Enhancing Students’ Digital Security Awareness through Data Protection and Phishing Prevention Education in a Secondary Education Institution - Wahyu Hidayat; Syahid Nur Wahid; Asmaul Husnah Nasrullah (PT. Global Research Collaboration, 2025)
Cybersecurity threats such as personal data breaches and phishing attacks are increasing alongside the widespread adoption of digital technologies among adolescents. This community engagement program aims to enhance digital literacy and cybersecurity awareness among students in a secondary education institution through education on personal data protection and phishing prevention. The activities included awareness sessions, training workshops, phishing simulations, and guided mentoring, using a participatory approach involving lecturers, university students, teachers, and learners. Evaluation results indicate a substantial improvement in participants’ understanding: over 75% of students were able to identify common phishing indicators, and 80% of teachers demonstrated an understanding of basic digital security principles. This initiative contributes to fostering a safer digital literacy culture and strengthening the technology-based learning ecosystem within secondary education.